Synthesis, electronic structure, DNA and protein binding, DNA cleavage, and anticancer activity of fluorophore-labeled copper(II) complexes - Bhat, Satish S.; Kumbhar, Anupa A.; Heptullah, Hussain; Khan, Ayesha A.; Gobre, Vivekanand V.; Gejji, Shridhar P.; Puranik, Vedavati G. (Inorganic Chemistry, 2011)
Two mononuclear fluorophore-labeled copper(II) complexes [Cu(nip)(acac)](+) (2) and [Cu(nip)(2)](2+) (3), where fluorophore is 2-(naphthalen-1-yl)-1H-imidazo[4,5-f][1,10]phenanthroline (nip) (1) and acac is acetylacetone, have been synthesized aid characterized by various techniques. The ligand 1 and complex 2 are structurally characterized by single-crystal X-ray diffraction. The coordination geometries around the copper are square planar in solid as well as solution state as evidenced by electron paramagnetic resonance (EPR) spectroscopy. The density functional calculations carried out on 1-3 have shown that electron-rich regions in the highest occupied orbital are localized on the naphthalene end partly on the phenanthroline moiety. Both complexes 2 and 3 in dimethyl sulfoxide (DMSO) exhibit near square planar structure around the metal ion in their ground state. Time-dependent density functional theory (TD-DFT) calculations reveal that Cu(II) ion in complex 2 shows tetrahedral coordination around the metal while 3 retains its square planar geometry in the lowest excited state. The interaction of complexes with calf-thymus DNA (CT DNA) has been explored by using absorption, emission, thermal denaturation, and viscosity studies, and the intercalating mode of DNA binding has been proposed. The complexes cleave DNA oxidatively without any exogenous additives. The protein binding ability has been monitored by quenching of tryptophan emission in the presence of complexes using bovine serum albumin (BSA) as model protein. The compounds showed dynamic quenching behavior. Further, the anticancer activity of the complexes on MCF-7 (human breast cancer), HeLa (human cervical cancer), HL-60 (human promyelocytic leukemia), and MCF-12A (normal epithelial) cell lines has been studied. It has been observed that 3 exhibits higher cytotoxicity than 2, and the cells undergo apoptotic cell death.

Water mediated proton conductance in a hydrogen-bonded Ni(II)-bipyridine-glycoluril chloride self-assembled framework - Tayade, Sakharam B.; Bhat, Satish S.; Illathvalappil, Rajith; Dhavale, Vishal M.; Kawade,Vitthal A.; Kumbhar, Avinash S.; Kurungot, Sreekumar; Näther, Christian (CrystEngComm, 2018)
Proton conducting properties have been investigated in a new Ni(II)-based hydrogen-bonded porous framework synthesized using a urea-fused bipyridine-glycoluril (BPG) tecton. This hydrogen-bonded self-assembled structure encapsulates water molecules in the channels with hydrogen-bonding networks which exhibits a significant temperature dependent proton conductance of 1.5 × 10−4 S cm−1 at 95 °C and 95% RH with a low activation energy (Ea) of 0.54 eV, implying a Grotthuss proton hopping mechanism mediated by hydrogen-bonded water molecules in the channels. In addition, this framework exhibited a very high water uptake under humid conditions. A continuous array of water molecules and chloride ions embedded in the highly hydrophilic porous channels of the hydrogen-bonded framework acts as the proton conducting medium.

Tris-heteroleptic ruthenium(II) polypyridyl complexes: Synthesis, structural characterization, photophysical, electrochemistry and biological properties - Bhat, Satish S.; Kumbhar, Avinash S.; Purandare, Neeraja; Khan, Ayesha; Grampp, Gunter; Loennecke, Peter; Hey-Hawkins, Evamarie; Dixit, Ruchi; Vanka, Kumar (Journal of Inorganic Biochemistry, 2020)
{Three water-soluble tris-heteroleptic ruthenium(II) polypyridyl complexes [Ru(bpy)(phen)(bpg)](2+) (1), [Ru (bpy)(dppz)(bpg)]2+ (2), and [Ru(phen)(dppz)(bpg)]2+ (3) (where bpy = 2,2'-bipyridine
Keywords: Circular dichroism; Cytotoxicity; fluorescence; Polypyridyl; ruthenium